2022
DOI: 10.1038/s41467-022-32500-z
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin-mediated iron detoxification promotes hypothermia survival in Caenorhabditis elegans and murine neurons

Abstract: How animals rewire cellular programs to survive cold is a fascinating problem with potential biomedical implications, ranging from emergency medicine to space travel. Studying a hibernation-like response in the free-living nematode Caenorhabditis elegans, we uncovered a regulatory axis that enhances the natural resistance of nematodes to severe cold. This axis involves conserved transcription factors, DAF-16/FoxO and PQM-1, which jointly promote cold survival by upregulating FTN-1, a protein related to mammali… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…C. elegans tightly regulates iron homeostasis through the control of iron transporter SMF-3, as well as the regulation of iron storage protein Ferritins FTN-1 and FTN-2 (Cha’on et al, 2007; Gourley, Parker, Jones, Zumbrennen, & Leibold, 2003; Kim, Cho, Yoo, & Ahnn, 2004; Pekec et al, 2022). Among the most differentially regulated genes, ftn-1 appeared to be consistently downregulated by H 2 S ( Figure 5A and B, Figure 5—figure supplement 1A–D ).…”
Section: Resultsmentioning
confidence: 99%
“…C. elegans tightly regulates iron homeostasis through the control of iron transporter SMF-3, as well as the regulation of iron storage protein Ferritins FTN-1 and FTN-2 (Cha’on et al, 2007; Gourley, Parker, Jones, Zumbrennen, & Leibold, 2003; Kim, Cho, Yoo, & Ahnn, 2004; Pekec et al, 2022). Among the most differentially regulated genes, ftn-1 appeared to be consistently downregulated by H 2 S ( Figure 5A and B, Figure 5—figure supplement 1A–D ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggest that, although PQM-1 nuclear exclusion by DAF-16 occurs only in daf-2 mutants but not under wild-type conditions, ETS-4 nuclear localization is hindered by DAF-16 even under wild-type conditions. ( Fig 3D , [ 6 , 23 ]).…”
Section: Resultsmentioning
confidence: 99%
“…ETS-4 contains both an ETS DNA binding domain and a PNT domain. Previous studies have shown that deleting ets-4 leads to a longer lifespan and increased cold tolerance [ 23 , 24 ]. However, ETS-4 is not always associated with negative effects in C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the beneficial effects of FUdR in promoting worms survival and protein turnover are not dependent on evolutionarily preserved transcriptional regulators DAF-13 16 and PQM-1, recognized for their cooperative role in enhancing resilience to cold conditions through the upregulation of FTN-1/ferritin (53). This delineates a distinct mechanistic route through which FUdR modulates cellular homeostasis and also raises intriguing questions about the potential cross-talk between various stress response pathways and how they might be selectively activated or bypassed.…”
Section: Discussionmentioning
confidence: 99%